13 secrets / 3. - Harrison, Michelle, 1979- (Thirteen Treasures, 2013)
Now living at Elvesden Manor under her real name of Rowan, Red attempts to put her past behind her, while fairy messengers try to convince her to participate once more in the changeling trade and she is haunted by dreams of an old enemy who is determined to exact his revenge.